Fighting for the soul of Germany : the Catholic struggle for inclusion after unification - Bennette, Rebecca Ayako, 1973- (Harvard historical studies, 2012)
Historians have long believed that Catholics were late and ambivalent supporters of the German nation. Rebecca Ayako Bennette's bold new interpretation demonstrates definitively that from the beginning in 1871, when Wilhelm I was proclaimed Kaiser of a unified Germany, Catholics were actively promoting a German national identity for the new Reich.